Association between different GLP-1 receptor agonists and gastrointestinal adverse reactions: A real-world disproportionality study based on FDA adverse event reporting system database - Liu, Lulu; Chen, Jia; Wang, Lei; Chen, Chen; Chen, Li (Frontiers in Endocrinology, 2022)
Objective: Glucagon-like peptide-1 receptor agonists (GLP-1 RAs) have significantly improved clinical effects on glycemic control. However, real-world data concerning the difference of gastrointestinal adverse events (AEs) among different GLP-1 RAs are still lacking. Our study aimed to characterize and compare gastrointestinal AEs among different marketed GLP-1RAs (exenatide, liraglutide, dulaglutide, lixisenatide and semaglutide) based on the real-world data. Methods: Disproportionality analysis was used to evaluate the association between GLP-1 RAs and gastrointestinal adverse events. Data were extracted from the US FDA Adverse Event Reporting System (FAERS) database between January 2018 and September 2022. Clinical characteristics, the onset time and severe proportion of GLP-1 RAs-associated gastrointestinal AEs were further analyzed. Results: 21,281 gastrointestinal toxicity reports were analyzed out of 81,752 adverse events reports, and the median age of included patients were 62 (interquartile range [IQR] 54–70) years old. Overall GLP-1 RAs was associated with increased risk of gastrointestinal system disorders (ROR, 1.46; 95%CI, 1.44-1.49), which were further attributed to liraglutide (ROR, 2.39; 95%CI, 2.28-2.51), dulaglutide (ROR, 1.39; 95%CI, 1.36-1.42) and semaglutide (ROR, 3.00; 95%CI, 2.89-3.11). Adverse events uncovered in labels included gastroesophageal reflux disease, gastritis, bezoar, breath odour, intra-abdominal haematoma, etc. Furthermore, it was observed that semaglutide had the greatest risk of nausea (ROR, 7.41; 95%CI, 7.10-7.74), diarrhoea (ROR, 3.55; 95%CI, 3.35-3.77), vomiting (ROR, 6.67; 95%CI, 6.32-7.05) and constipation (ROR, 6.17; 95%CI, 5.72-6.66); liraglutide had the greatest risk of abdominal pain upper (ROR, 4.63; 95%CI, 4.12-5.21) and pancreatitis (ROR, 32.67; 95%CI, 29.44-36.25). The majority of gastrointestinal AEs tended to occur within one month. Liraglutide had the highest severe rate of gastrointestinal AEs (23.31%), while dulaglutide had the lowest, with the severe rate of 12.29%. Conclusion: GLP-1 RA was significantly associated with gastrointestinal AEs, and the association were further attributed to liraglutide, dulaglutide and semaglutide. In addition, semaglutide had the greatest risk of nausea, diarrhoea, vomiting, constipation and pancreatitis, while liraglutide had the greatest risk of abdominal pain upper. Our study provided valuable evidence for selecting propriate GLP-1 RAs to avoid the occurrence of GLP-1 RAs-induced gastrointestinal AEs.